InFORM: Improving care for people who Frequently call 999: co-production of guidance through an Observational study using Routine linked data and Mixed methods - Khanom, Ashrafunessa; Edwards, Adrian; Edwards, Bethan; Hughes, Heather; John, Ann; Petterson, Robin; Phillips, Ceri; Porter, Alison; Rees, Nigel; Scott, Jason; Watkins, Alan; Snooks, Helen (International Journal of Population Data Science, 2019)
Background People who frequently call the 999 ambulance service present an operational challenge to providers and their needs are inadequately met by current service provision. Aim of research To understand patterns and health outcomes of frequent calling and to work with stakeholders to co-produce guidance for formal testing in a future evaluation. Methods This mixed methods study will include a scoping review of national and international literature followed by an epidemiological study of callers at the all Wales level exploring health outcomes through anonymised linked data. We will also explore the views of patients using qualitative Bio-photographic interview method with a follow up interview at six months and use focus groups with care providers from across primary and emergency care and the third sector. We will use generalised linear model to analyse quantitative data and qualitative data will be analysed thematically. Results Findings will include follow up of eligible patients; successful data matching and data linkage; retrieval of outcomes within 12 months. Outcomes will include: adverse events, deaths, emergency admissions; 999 attendances. Qualitative results will include Bio-photographic interviews with completed scrap books and interviews based on the books (n=34). Care provider focus groups (n= 22). Output Co-produced guidance developed with stakeholders. Conclusion High users of the 999-ambulance represent a significant policy challenge to emergency ambulance services and often present with complex needs. This study will inform on the characteristics of callers and how to address their care supported with a co-produced guidance for care providers.